PENGARUH KUAT MEDAN MAGNET DAN LAMA PERENDAMAN TERHADAP PERKECAMBAHAN PADI (Oryza sativa L.) KADALUARSA VARIETAS CIHERANG - Yuhelsa Putra; Tubagus Bahtiar Rusbana; Wulan Anggraeni (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2014)
This research was aimed to know the effect of magnetic field strenght and duration of Immersion on Germination of ExpiredRice (Oryza sativa L.) Seed of Ciherang Variety. This research used a Randomized Complete Design with two factors. The first factor was magnetic field strenght (M) consisting of four levels, namely: M0 (0 mT), M1 (15 mT), M2 (20 mT) and M3 (25 mT). The second factor was duration immersion in magnetized water (T), which consists of three levels, namely: T1 (12 hours), T2 (24 hours) and T3 (36 hours). The combination treatment was repeated three times, so there was 36 experimental units. Observed variables were germination age (days), the maximum growth potential (%), growth rate (%/day), normal germination percentage (%) and abnormal germination percentage (%). The result showed that magnetic field strenght and magnetized water is not able to improved for all observed variables were germination age (days), maximum growth potential (%), growth rate (%/day), normal germination percentage (%) and abnormal germination percentage (%). There was an interaction between the magnetic field strenght and duration of immersion time. The interaction magnetic field strenght of 0 mT and 15 mT with 12 hours and 20 mT with 24 hours immersion. Improved the growth rate and normal germination percentage by 0,95 %/day and 13,33% consecutively.